2016
DOI: 10.1016/j.electacta.2016.07.146
|View full text |Cite
|
Sign up to set email alerts
|

Covalent silica-PEO-LiTFSI hybrid solid electrolytes via sol-gel for Li-ion battery applications

Abstract: Organic/inorganic hybrid membranes based on (3-glycidoxypropyl) trimethoxysilane (GPTMS) and ethylene glycol diglycidyl ether (EGDE), have been prepared by sol-gel method and organic polymerization as solid electrolytes for Li-ion batteries. Lithium bis(trifluoromethane)sulfonamide (LiTFSI) was used as Li salt. FTIR and Raman spectroscopies were used to confirm the hybrid structure formation and the interactions between Li ions and hybrid network. An Arrhenius-like temperature dependence of ionic conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 62 publications
2
45
0
1
Order By: Relevance
“…So, the addition of inorganic part (SiO 2 ) in PEO leads to the formation of Si–O–Si skeleton in the polymer matrix which imparts thermal and mechanical stability to the hybrid films. The small bands obtained at ∼ 755, 693 and 787 cm −1 has been assigned to SiOCH 3 bending, OSiO and symmetric SiOSi stretching vibrations, respectively . Moreover, the vibrational bands obtained at 844, 948, 1062, 1148, 1280, 1344, 1468 cm −1 in pure PEO are found to shift in PI to 841, 947, 1059, 1145, 1279, 1343, and 1466 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…So, the addition of inorganic part (SiO 2 ) in PEO leads to the formation of Si–O–Si skeleton in the polymer matrix which imparts thermal and mechanical stability to the hybrid films. The small bands obtained at ∼ 755, 693 and 787 cm −1 has been assigned to SiOCH 3 bending, OSiO and symmetric SiOSi stretching vibrations, respectively . Moreover, the vibrational bands obtained at 844, 948, 1062, 1148, 1280, 1344, 1468 cm −1 in pure PEO are found to shift in PI to 841, 947, 1059, 1145, 1279, 1343, and 1466 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 79%
“…The de‐convoluted spectra confirmed the existence of two peaks in all PINa 10 IL x hybrid electrolytes. The first one located at 739 cm −1 corresponds to the fraction of free TFSI − anions while the second one at 742 cm −1 corresponds to the contact ion‐pair formation between Na + …TFSI − or HMIM + …TFSI − …”
Section: Resultsmentioning
confidence: 99%
“…In Figure a we present the vibrational spectrum and the relevant vibration assignments of the neat TmdSx‐CN solvent, and of the electrolyte solution (1 mol kg −1 LiTFSI in TmdSx‐CN) recorded by attenuated total reflection–Fourier transform infrared spectroscopy (ATR‐FTIR) . To test the chemical stability of both solutions to oxygen and moisture we exposed both (neat disiloxane, and electrolyte) to the atmosphere for 10 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrolyte absorbs water because of the hygroscopic LiTFSI, which is evident by the presence of two characteristic broad residualwater peaks at 1630 cm À1 and 3500 cm À1 (refer to Supporting Information, Figure S3). [33][34][35] To characterize the composition of the SEI on the silicon nanostructure anodes under cycling conditions, we applied polarization-modulation infrared-reflectance absorption spectroscopy (PM-IRRAS). We scanned two electrolyte compositions -with and without 10 %(wt) FEC -at open-circuit voltage (OCV), and after cycling.…”
Section: Figurementioning
confidence: 99%
“…Very recently, Cui et al reported that monodispersed SiO 2 nanospheres were incorporated into PEO polymer electrolyte via an in situ synthesis to significantly suppress the crystallization and thus facilitate chain segments mobility [33]. Moreover, there were other recent trends in this direction, such as biopolymers [40], composites [41] and semi-interpenetrating networks (ITN) electrolytes [42,43]. Inspired by the advantages of the conventional liquid carbonate electrolytes readily decomposed into polycarbonate species and resulting in stable SEI on both electrodes [2], polycarbonate-based electrolytes have recently attracted great interests in lithium battery field.…”
Section: Introductionmentioning
confidence: 99%